The Role of Psychology of Law in Legal Protection of Children as Criminal - Widya Romasindah Aidy (Siber International Journal of Advanced Law (SIJAL), 2024)
Children who are in conflict with the law both as perpetrators and victims must be protected by the government and must not be treated in a discriminatory manner. The purpose and benefit of this study is to understand and know the role of psychology of law on legal protection for children as perpetrators of criminal acts. In this study, the Research Method used is normative juridical research with a statute approach, conceptual approach and examines the handling of cases of children conflict with the law not only using a legal approach but an extrajudicial approach, namely psychological science which in this study is focused on psychology and law. There is also a form of legal protection for children conflict with the law can not only be resolved through the judicial process, but can also be resolved through diversion, where the settlement involves the perpetrator, victim, and family, both the perpetrator/victim's family and related parties to jointly seek a fair solution by emphasizing restoration to the original situation, and not by means of retaliation known as the restorative justice. The role of psychology of law for children criminal acts can be given from the time the child is examined at the Police until the child undergoes coaching at Lembaga Pembinaan Khusus Anak.